Fluoride Binding and Crystal‐Field Analysis of Lanthanide Complexes of Tetrapicolyl‐Appended Cyclen. Issue 26 (11th May 2016) - Blackburn, Octavia A.; Kenwright, Alan M.; Jupp, Andrew R.; Goicoechea, Jose M.; Beer, Paul D.; Faulkner, Stephen
Abstract: Lanthanide complexes of tetrapicolyl cyclen displayed remarkably high affinities for fluoride (log K ≈5) in water, and were shown to form 1:1 complexes. The behaviour of these systems can be rationalised by changes to the magnitude of the crystal‐field parameter, B 2 0 . However, such changes are not invariably accompanied by a change in sign of this parameter: for early lanthanides, the N8 donor set with a coordinated axial water molecule ensures that the magnetic anisotropy has the opposite sense to that observed in the analogous dehydrated lanthanide complexes. Abstract : Magnetic anisotropy : This study shows the importance of the local crystal field in defining the behaviour of lanthanide complexes in solution. The observation that a well‐defined N8 donor set can be used to change the sense of the magnetic anisotropy at a lanthanide centre has significant implications for control of spectroscopic properties in such systems (see scheme).